2017
DOI: 10.1002/jssc.201700507
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of potential hypoglycemic components in Zeng Ye Tang by high‐performance liquid chromatography coupled with tandem quadrupole time‐of‐flight mass spectrometry

Abstract: Zeng Ye Tang, a famous prescription consisting of Xuanshen, Maidong, and Shengdi (5:4:4), has been used in China for a long time to treat diabetes caused by excessive heat with yin deficiency. Although many studies have investigated the pharmacological effects of Zeng Ye Tang, the compounds responsible for its hypoglycemic effect have not been identified. In this study, 50 compounds in Zeng Ye Tang were identified by high-performance liquid chromatography coupled with tandem quadrupole time-of-flight mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Angoroside C (Figure 1 ) is a representative phenylpropanoid glycoside (PhG) compound isolated from Scrophularia ningpoensis Hemsl ( Li et al, 2000 ; Wagner et al, 2011 ). Which possesses the ability to reduce blood pressure ( Liu et al, 2015 ), and has anti-inflammatory ( Díaz et al, 2004 ), anti-platelet aggregation ( Cano et al, 1990 ), hepatoprotection ( Huang et al, 2004 ; Morikawa et al, 2010 ), and hypoglycemic properties ( Tian et al, 2017 ), as well as being able to reduce pulmonary oedema ( Zhang et al, 2017 ). Furthermore, according to the continuous series of in-depth studies by Gu Weiliang on Radix Scrophulariae ( Gu et al, 2010 ; Huang et al, 2012 ), the results showed that angoroside C has beneficial effects against ventricular remodeling, and the mechanism is likely to be related to decreasing the level of Ang II, attenuating the mRNA expressions of endothelin 1 (ET-1) and transforming growth factor β1 (TGF-β1) ( Gu et al, 2015 ), which is effective in postponing heart failure for patients with cardiovascular illness.…”
Section: Introductionmentioning
confidence: 99%
“…Angoroside C (Figure 1 ) is a representative phenylpropanoid glycoside (PhG) compound isolated from Scrophularia ningpoensis Hemsl ( Li et al, 2000 ; Wagner et al, 2011 ). Which possesses the ability to reduce blood pressure ( Liu et al, 2015 ), and has anti-inflammatory ( Díaz et al, 2004 ), anti-platelet aggregation ( Cano et al, 1990 ), hepatoprotection ( Huang et al, 2004 ; Morikawa et al, 2010 ), and hypoglycemic properties ( Tian et al, 2017 ), as well as being able to reduce pulmonary oedema ( Zhang et al, 2017 ). Furthermore, according to the continuous series of in-depth studies by Gu Weiliang on Radix Scrophulariae ( Gu et al, 2010 ; Huang et al, 2012 ), the results showed that angoroside C has beneficial effects against ventricular remodeling, and the mechanism is likely to be related to decreasing the level of Ang II, attenuating the mRNA expressions of endothelin 1 (ET-1) and transforming growth factor β1 (TGF-β1) ( Gu et al, 2015 ), which is effective in postponing heart failure for patients with cardiovascular illness.…”
Section: Introductionmentioning
confidence: 99%
“…The model of T2DM rats was induced by high-fat diet combined with low-dose STZ (35 mg/kg) [16]. The method was improved according to the previous reports and laboratory studies [10,17]. Briefly, the animals were fed a high-fat diet for 3 weeks followed by intraperitoneal injection of STZ (35 mg/kg) which dissolved in cold citrate buffer (pH 4.3, 0.05 M).…”
Section: Preparation Model Of T2dm Rats and Drug Administrationmentioning
confidence: 99%
“…There have been some researches on the chemical constituents and herbal ingredients of ZYD in previous studies [9,10]. A few reports have studied the absorption of a few compounds of ZYD [11].…”
Section: Introductionmentioning
confidence: 99%
“…Differently, Tian's team identifi ed 50 ingredients in Zeng Ye Tang in vitro, then nine compounds were identifi ed by 3T3-L1 adipocytes due to interacting with cells. Further, the potential effective compounds were detected in the blood through SPT analysis between normal and diabetic rats after dosing of Zeng Ye Tang, the result was that six shared prototype constituents had been verifi ed to have anti-diabetic effects on type 2 diabetic mice, they were catalpol, harpagide, p-coumaric acid, harpagoside, angoroside C, cinnamic acid , some of which including harpagide, harpagoside, angoroside C, and cinnamic acid were from Xuanshen; catalpol, p-coumaric acid and acteoside were from Shengdi; methylophiopogonanone A and methylophiopogonanone B were from Maidong [73] .The similar mode of research was used by Han. In the literature, Han's team constructed a comprehensive way by using UHPLC-FT-ICR-MS and SPT technique to discover the effective compounds of Zhi-Zi-Da-Huang decoction (ZZDHD) which can detoxify hepatotoxicity in alcohol-induced rats after dosing.…”
Section: Rec Ent Applicationsmentioning
confidence: 99%